Development of an Evidence-Based First Aid Guideline for First Responders in Sub-Saharan Africa - Bert Avau (International Journal of First Aid Education)
Background: Many Sub-Saharan African countries lack effective emergency medical services. In response, Red Cross and Red Crescent National Societies, amongst other organizations implement first responder training programs across Africa. The current paper describes the development of an advanced manual for first responders (FAFR) in Sub-Saharan Africa. Methods: This FAFR manual was developed according to the principles of Evidence-Based Practice accounting for scientific evidence, expert opinion, and preferences of the target audience (i.e., Sub-Saharan African first responders). The GRADE (Grading of Recommendations Assessment, Development, and Evaluation) approach was used to assess the certainty of evidence. A geographically balanced expert panel of African field and academic experts set the scope and defined the research questions. The best available evidence was systematically collected and presented to independent and dedicated content writers, drafting the manual. The expert panel discussed these draft recommendations during a two-day meeting and validated the final version of the manual. Results: The systematic literature addressed 87 research questions. Of these, 52 could be supported by scientific evidence, in thirteen cases by a Cochrane systematic review. We determined the GRADE certainty of the evidence as low (38%) or very low (53%). Where no evidence was found, good practice points were formulated based on expert opinion. Conclusions: The FAFR manual is used by Red Cross and Red Crescent National Societies across Africa and will be updated every five years by the Belgian Red Cross. The manual is freely available to anyone interested (https://www.rodekruis.be/en/what-do-we-do/first-aid-and-support/first-aid-for-first-responders/).